The use of tucumã oil (Astrocaryum vulgare) in alloxan-induced diabetic mice: effects on behavior, oxidant/antioxidant status, and enzymes involved in brain neurotransmission - Baldissera M.D. (2017)
© 2017, Springer Science+Business Media New York.The aim of this study was to investigate the effects of tucumã oil (Astrocaryum vulgare) on memory, enzymatic activities of sodium–potassium pump (Na+, K+-ATPase) and acetylcholinesterase (AChE) in the brain of alloxan-induced diabetic mice. The animals were divided into four groups (n = 6 each): the group A (non-diabetic/water), the group B (non-diabetic/tucumã oil), the group C (diabetic/water), and the group D (diabetic/tucumã oil) treated 14 days with 5.0 mL kg−1 via oral gavage. Untreated diabetic mice (the group C) showed memory deficit, increased levels of thiobarbituric acid reactive species (TBARS) and protein carbonylation (PC), and decreased (p < 0.05) catalase (CAT), superoxide dismutase (SOD), and the Na+, K+-ATPase activities, while acetylcholinesterase (AChE) activity showed a significant increase (p < 0.05) compared to non-diabetic mice (the group A). Tucumã oil prevented these alterations in diabetic mice treated with tucumã oil (the group D) compared to diabetic mice (the group C). Our findings suggest that tucumã oil can modulate cholinergic neurotransmission resting membrane potential of neurons by modulating enzymatic antioxidant defenses. In conclusion, the present data showed that treatment with tucumã oil is beneficial to diabetic mice, demonstrating that this oil can modulate cholinergic neurotransmission and consequently improve or avoid memory deficits.